CONCEPTUAL METAPHORS IN AMERICAN JOURNALISTIC TEXTS - Anatoliy Khudoliy (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The article is dedicated to representation and functions of tropes in American journalistic texts, their semantic and cognitive features. The figurative language under analysis is a reflection of American politicians' language, in particular their everyday metaphors. Not only do we examine the main aspects of figurative language associated with aquatic habitat used by American politicians in public discourse, but we also rely upon an approach based on conceptual metaphor theory when we analyse and classify conceptual metaphors related to water. The object of cognitive analysis is political texts in American newspapers and magazines. The author provides a linguistic analysis of conceptual metaphors, their functions and application. Metaphors serve as indicators of functional changes in American English. Cognitive aspects of metaphors are being discussed. According to the theory of cognitive linguistics, a metaphor is an integral part of the cognitive process and an instrument that expresses and forms new notions. American politicians often use metaphors to affect the unconscious minds of the people. The research results show that the most frequently used conceptual metaphors in the analysed corpora are the linguistic realisations of metaphors from the source domain of aquatic habitat. All the metaphors of this group are classified into subgroups according to the key semantic component. A deep consideration is given to aquatic metaphors and reasons of their topicality.